(untitled) (Research, Society and Development, 2022)
Although there are different methodologies for collection of microorganisms from hands, there is a lack of comparative studies. In this sense, we aimed to quantify potential pathogenic strains in the hands of nursing professionals in a public hospital in South of Brazil, based on the comparative evaluation of collection methods. For this, we carried out a cross-sectional, experimental and quali-quantitative study, during 2019, under the approval of the Ethics and Research Committee with Human Beings. We proved that glove-juice is the recommended methodology for microbiological collections from the hands, as it recovered 42.19% of the microorganisms, while the swab recovered 1.91%. From this, we carried collections, quantification and identification of microorganisms in the hands of nursing professionals. For mesophilic aerobic microorganisms, the quantification ranged from 5X104 to 4X106 CFU/hand, for coagulase positive Staphylococcus ranged from 5X104 to 3X106 CFU/hand and for fungi from 5X104 to 2X106 CFU/hand. Among the fungi, yeasts dominated in 93.73%, being frequently identified the genus Candida spp. Total and thermotolerant coliforms were not found. Staphylococcus aureus were in 90.91% of the hands, and the Antibiotic Sensitivity Test was carried out in 25 isolated colonies, all testing resistance to at least three classes of antibiotics, showing that they are multiresistant. Data analysis showed that the best collection method is glove-juice, as it recovers greater quantity and microbial diversity than the compared method. In addition, it was possible to observe the importance of hands as sources of cross-contamination between patients.